The Role of Government in Reducing Stunting - Nur Hidayatul Rokhmah; Sri Kamariyah; Ika Devy Pramudiana; Kristyan Dwijosusilo (Institute of Advanced Knowledge and Science, 2024)
This study aims to analyze the role of the government in efforts to reduce the prevalence of stunting in Driyorejo District, Gresik Regency, with a focus on the implementation of the Foster Father Program and Food Assistance. Stunting, which is caused by chronic malnutrition, has a negative impact on child growth and development and is one of the main health problems in Indonesia. This study uses a qualitative descriptive approach with data collection through in-depth interviews, observation, and documentation. The results show that the government plays an active role in facilitating synergy between various parties, including the community, private sector, and local government institutions, to reduce stunting rates. On the other hand, the Food Assistance program focuses on the distribution of nutritious food to families at risk of stunting, in collaboration with institutions such as the Post Office and Baznas. Both programs are equipped with periodic measurements of child growth by health cadres using adequate tools. The conclusion of this study confirms that the role of the government in Driyorejo District, through strengthening cross-sector coordination and community participation, has had a positive impact on reducing the prevalence of stunting. However, the sustainability of this program requires budget support, community education, and ongoing evaluation to ensure long-term effectiveness.